Regional Landuse in Iran Based on SWOT Index (a Case Study: Iran-Iraq Frontier) - Hassan Nami, Muhammad; Semnani, Alireza Abbasi (International Journal of Bio-resource and Stress Management, 2012)
In today’s world, land is considered as one of the scarce gifts, so there is a competition between different human activities including farming and gardening, forest and pasture, industry and mine, city and village and the like. Wise allocation of land to these activities is one of the land-use discussions. On the other hand, land-use comprises adjusting the relationship between human, space and human activities in the space aiming at logical exploitation of all facilities to improve material and spiritual status of the society in the long run. Since regional land-use and planning is in fact a process forming from the interaction between natural and human made functions in geographical space, now viewing regional land-use in Islamic Republic of Iran and Turkamanestan frontline, present article is formulated.